Heat Transfer Augmentation in the Straight Channel by Using Nanofluids - M. Kh., Abdolbaqi; C. S. N., Azwadi; R., Mamat (Elsevier, 2014)
Heat transfer enhancement of nanofluids under turbulent flow through a straight square channel under constant heat flux conditions at the upper and lower walls is studied numerically. The nanofluids are prepared as solid nanoparticles of CuO, TiO2 and Al2O3 suspended in water. CFD analysis by FLUENT software using the finite volume method is conducted. The boundary conditions are applied under a heat flux of 5000 W/m2, Reynolds numbers of 104–106 and a constant volume concentration of 1–4%. The results show that the heat transfer rates and wall shear stress increase with an increase of the nanofluids’ volume concentration. It seems that the CuO nanofluid significantly enhances heat transfer. The results show good agreement with results of other researchers by a 10% deviation.